Not only summer matters: spring warming shapes the gorgonian condition when facing marine heatwaves - DEL ALCÁZAR-JULIÀ, AINA; VILADRICH, NÚRIA; GORI, ANDREA; LINARES, CRISTINA (Mediterranean Marine Science, 2025)
Accelerated spring warming is one of the less studied consequences of global change. This study aimed to evaluate the effects of an accelerated increase in seawater temperatures during spring on respiration and zooplankton capture rates, as well as the resulting nutritional condition of one of the main structural species of coastal Mediterranean benthic communities, the red gorgonian Paramuricea clavata. Fragments of red gorgonian colonies were maintained in aquaria under historical and accelerated spring temperature rises. While P. clavata was able to acclimate and maintain constant respiration rates during historical spring conditions, accelerated warming resulted in significantly higher respiration rates. Conversely, the zooplankton capture capacity was not affected. As a result, gorgonians were significantly depleted in organic matter and overall energy content after accelerated spring warming. These results highlight the crucial role of spring thermal conditions in shaping the health condition of P. clavata when facing high summer temperatures, and potential heatwaves.